One step synthesis of magnetic particles covered with casein surfactant (2014)
ABSTRACT: The one-step coprecipitation method is used to obtain magnetic nanoparticles controlling the pH (10 and 12), and casein surfactant (CS) concentrations (1 % and 3 % (m/m)). CS has not been used so far for stabilizing magnetic iron oxide ferrofluids. The magnetic nanoparticles have a magnetite core with maghemite in surface, and a shell of polymer. The transmission electron images confirm the crystallinity, particle size distribution in the range of 5-10 nm, and the spinel structure of the nanoparticles. Mössbauer results at 80 K showed line shapes dominated by magnetic relaxation effects with sextets and combinations of sextets and doublets. The interactions of the surfactant with the nanoparticle surface are strong showing at least two surfactant layers. The magnetic behavior was evaluated by moment versus temperature and magnetic field measurements. The nanoparticles showed superparamagnetic behavior at room temperature and blocked (irreversible) behavior at 5 K. The saturation magnetization presented lower values than reported bulk systems due to the presence of a large layer of maghemite. The FC/ZFC magnetization vs. temperature curves confirmed the superparamagnetic nature of the iron oxide particles and the strong interactions for pH 12 samples and weak interactions for pH 10 samples. The particle growth was dominated by the surface properties of the nanoparticles.